Maternal depressive symptoms trajectories and harsh parenting: the mediating role of maternal quality of life in the 2004 Pelotas Birth Cohort - Alicia Matijasevich; Jessica Mayumi Maruyama; Luciana Tovo-Rodrigues; Iná S. Santos (Brazilian Journal of Psychiatry)
Objective: To study the impacts of maternal depressive symptoms trajectories and harsh parenting and explore if the maternal quality of life (QoL) mediates this association. Methods: We used data from the 2004 Pelotas Birth Cohort, a population-based longitudinal study from Pelotas, Brazil (n=3,285 mothers, complete cases analysis). We used the Edinburgh Postnatal Depression Scale (EPDS) to assess maternal depressive symptoms and calculated their trajectories from 3 months until the 11-year follow-up using a group-based modeling approach. Psychological and physical aggression were measured using the Parent-Child Conflict Tactics Scale (CTSPC). Maternal QoL was measured by the question “How is your quality of life?” Data were analyzed using path models in Mplus. Results: All maternal depressive symptoms trajectories increased the frequency of psychological and physical aggression at early adolescence when compared to the reference group. Mediation analysis indicated that maternal depressive symptoms led to low levels of perceived maternal QoL, which in turn was associated with increased use of harsh parenting. The proportion of total effect explained by maternal QoL ranged from 4.04% (0.00-5.58%) to 16.31% (10.88-19.10%). Conclusion: Our findings, within a longitudinal framework from a middle-income country, support existing evidence that maternal depressive symptoms are associated with harsh parenting. Our results also suggest that one mechanism underlying this association is lower perceived maternal QoL.